Experimental determination of tram electric drive equivalent loading static moment and equivalent moment of inertia adduced to relative axis - Mokin, O. B. (Visnyk of Vinnytsia Politechnical Institute, 2010)
Using earlier created methods the tram (KT4SU) electric drive equivalent loading static moment and equivalent moment of inertia adduced to relative axis rotated with the angular velocity of the tram electric motors (TE022) was determined.